Mentorship in academic medicine - Straus, Sharon E.; Sackett, David L. (Chichester, West Sussex : John Wiley & Sons, 2014)
Mentorship in Academic Medicine is an evidence-based guide for establishing and maintaining successful mentoring relationships for both mentors and mentees. Drawing upon the existing evidence-base on academic mentoring in medicine and the health sciences, it applies a case-stimulus learning approach to the common challenges and opportunities in mentorship in academic medicine. Each chapter begins with cases that take the reader into the evidence around specific issues in mentorship and provides actionable messages and recommendations for both correcting and preventing the.
What is the evidence for mentorship? -- What are the characteristics and behaviors of effective mentors and mentees? -- How can you initiate mentorship? -- Some effective mentoring strategies and tactics : part 1, mentorship meetings, priority setting, and time-management -- Some effective mentoring strategies and tactics : part 2, protecting mentees from dys-opportunities -- Some effective mentoring strategies and tactics : part 3, mentoring for knowledge generation -- Some effective mentoring strategies and tactics : part 4, mentoring for knowledge dissemination -- Some effective mentoring strategies and tactics : part 5, mentoring for promotion, protection, and job prospects -- How can you assess, diagnose and treat mentorship that is in trouble? -- How can you initiate and maintain a mentorship progam? -- How can you evaluate the impact of a mentorship program? -- How can you scale up and sustain a mentorship program?.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Mentors; Education, Medical; Faculty, Medical; HEALTH & FITNESS / Holism; HEALTH & FITNESS / Reference; MEDICAL / Alternative Medicine; MEDICAL / Atlases; MEDICAL / Essays; MEDICAL / Family & General Practice; MEDICAL / Holistic Medicine; MEDICAL / Osteopathy; Mentoring in medicine; Medical education; Medical education; Mentoring in medicine; Education, Medical; Faculty, Medical; Mentoring in medicine; Mentors; Electronic books